Biomechanical evaluation of different strain judging criteria on the prediction precision of cortical bone fracture simulation under compression - Fan, Ruoxun; Liu, Jie; Jia, Zhengbin (Frontiers in Bioengineering and Biotechnology, 2023)
Current simulation analyses mainly apply the principal strain or equivalent strain to judge the mechanical state of the element in the cortical bone finite element model and then perform fracture simulation. However, no general strain judging criterion for simulating the cortical bone fracture was provided, so which type of strain is more suitable for judging the element mechanical state under different loading conditions is not clear. This study aimed to perform fracture simulation on the rat femoral cortical bone based on continuum damage mechanics theory to explore the suitable strain judging criterion in compression condition. The principal strain and equivalent strain were separately used to judge the mechanical state in the element of cortical bone finite element model to conduct fracture simulation. Then, the simulation results were compared with the corresponding experimental data to determine the fracture prediction accuracy. Results showed that the fracture parameters predicted by applying the principal strain were closer to the experimental values than those predicted by the equivalent strain. Therefore, the application of the principal strain to control the damage and failure state in the element to perform fracture simulation was more accurate under compression. This finding has the potential to improve the prediction accuracy in the cortical bone fracture simulation.